Variation and covariation in strongyle infection in East African shorthorn zebu calves - Callaby, R.; Hanotte, Olivier H.; Wyk, Ilana Conradie van; Kiara, Henry K.; Toye, Philip G.; Mbole-Kariuki, Mary N.; Jennings, A.; Thumbi, Samuel M.; Coetzer, Jacobus A.W.; Bronsvoort, B.M. de C.; Knott, S.A.; Woolhouse, Mark E.J.; et al. (Cambridge University Press, 2015)
Parasite burden varies widely between individuals within a population, and can covary with multiple aspects of individual phenotype. Here we investigate the sources of variation in faecal strongyle eggs counts, and its association with body weight and a suite of haematological measures, in a cohort of indigenous zebu calves in Western Kenya, using relatedness matrices reconstructed from single nucleotide polymorphism (SNP) genotypes. Strongyle egg count was heritable (h2 = 23·9%, s.e. = 11·8%) and we also found heritability of white blood cell counts (WBC) (h2 = 27·6%, s.e. = 10·6%). All the traits investigated showed negative phenotypic covariances with strongyle egg count throughout the first year: high worm counts were associated with low values of WBC, red blood cell count, total serum protein and absolute eosinophil count. Furthermore, calf body weight at 1 week old was a significant predictor of strongyle EPG at 16–51 weeks, with smaller calves having a higher strongyle egg count later in life. Our results indicate a genetic basis to strongyle EPG in this population, and also reveal consistently strong negative associations between strongyle infection and other important aspects of the multivariate phenotype.